Plastic deformation of AA6061-T6 at elevated temperatures: Experiments and modeling. (15th February 2022) - Roy, Biplov Kumar; Korkolis, Yannis P.; Arai, Yoshio; Araki, Wakako; Iijima, Takafumi; Kouyama, Jin
Highlights: The work-hardening of AA6061-T6 between room temperature to 500 °C is investigated. Diffuse necking is observed early on in the elevated temperature tests. The work-hardening curves are identified using a finite element model of necking. Rate-dependence is necessary for the work-hardening curves at elevated temperatures. Swift/Voce with Johnson-Cook strain-rate dependence is sufficient and very accurate. Abstract: The temperature-dependent work-hardening of AA6061-T6 aluminum alloy is investigated using a combined experimental-numerical approach. Uniaxial tension experiments are performed from room temperature to 500 °C, and the force-displacement curves up to fracture are established. Both the yield strength and the work-hardening rate of the material decrease with increasing temperature. Despite the marked increase in the elongation-to-fracture, the uniform elongation remains limited, indicating the early appearance of diffuse necking in the elevated temperature tests. A simplified technique for identifying the work-hardening curves at elevated temperatures and beyond the limit of uniform deformation in uniaxial tension is proposed. The technique uses an isothermal, rate-dependent, finite element (FE) model of the experiments. The post-necking hardening curve is represented by a hybrid Swift/Voce hardening law combined with a form of Johnson-Cook strain-rate dependence. To identify the material model parameters at each temperature, an objective function that correlates the experimental and FE-predicted force-displacement curves is constructed and minimized. These model parameters are then fit with Fourier series across the temperature range considered here, providing smooth functions suitable for subsequent implementation in FE analyses of forming and structural problems. As an illustration, it is shown that a FE model utilizing these material parameters reproduces the full-field features of the elevated temperature experiments very well. Graphical abstract: Image, graphical abstract